PENTINGNYA LITERASI KEUANGAN UNTUK PENGELOLAAN KEUANGAN PRIBADI SEJAK DINI - Marchyta, Nony Kezia; Sutanto, Eddy Madiono (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
The younger generation's low level of financial literacy and the increasing use of online lending (pinjol) encourage this community service activity. Community service aims to increase awareness of the importance of financial literacy for the younger generation in managing finances to improve self-control. Young people with good financial literacy tend to prioritize making financial decisions, including being able to distinguish between their needs and wants. Conversely, if the younger generation needs better financial literacy, they will tend to make mistakes in financial management that can have a negative impact in the long run. Community service partners are young people aged 15 to 21 under the auspices of the Adjarmanu Foundation, East Nusa Tenggara, and Child Development Centers in Surabaya and Sidoarjo. Community service is carried out using training methods. The material provided uses the concept of gamification to make it more attractive to the younger generation. The results of the post-test show that the financial literacy skills of the participants have increased. A positive response from the participants was also seen in a brief interview conducted at the end of the community service activity.